Gold deportment and ore characterisation of the historical Witwatersrand tailings dams with emphasis placed on the sulphides - Chingwaru, Steve Jason (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.